Development of Mathematics Learning Video Media Based on Realistic Mathematics Education (RME) in Grade V at MIN 1 Serang - Iis, Iis Rohmayanti; Sari Dewi, Ratna; Adya Pribadi, Reksa (Jurnal Primagraha, 2024)
This research aims to develop a Mathematics learning video media based on Realistic Mathematics Education (RME) with the involvement of teachers in the development process and testing the effectiveness of the media product through the expert testing stage and to find out how students respond to the Realistic Mathematics Education (RME) based Mathematics learning video media. ) were developed. This research uses the Research & Development (R&D) research method using the ADDIE model, with several stages, namely Analysis, Design, Development, Implementation, Evaluation. This research was conducted at MIN 1 Serang with 27 VA class students as research subjects with details of students in limited trials. The instrument used is a questionnaire sheet for validation of material experts, media experts and language experts as well as student responses. The research results obtained were the feasibility of Realistic Mathematics Education (RME)-based Mathematics learning video media based on expert assessment, obtaining the criteria "Very Feasible", with a percentage of material experts of 93.68%, media experts of 88.95% and language experts of 83%. Students gave a positive response with a percentage of 95.18% and were included in the "Very Good" category. The development of Realistic Mathematics Education (RME)-based Mathematics learning video media is very suitable for use and has received a positive response to be used as a learning medium.